Penerapan Desain UI/UX dalam Pengembangan Aplikasi Administrasi Keuangan Logistik untuk Efisiensi Operasional di PT Prima Cipta Express dengan Metode Design Thinking - Teguh Satriyo; Jeffri Alfa Razaq (Sekawan Institut, 2024)
In the current digital era, information technology and software applications are important for increasing operational efficiency in the business world, especially in the fields of logistics and financial management. Ineffective management of logistics financial administration can result in increased costs, delays in delivery, and even inaccuracies in financial reports. Therefore, this research was conducted with the aim of overcoming operational efficiency challenges for PT Prima Cipta Express. One approach that can be taken to overcome this challenge is to apply the Design Thinking method which includes the Empathize, Define, Ideate, Prototype and Test stages. At the testing stage, this research uses usability testing and SUS (System Usability Scale) calculations which are useful for testing prototype usability. This research, testing involved a prototype user experience using Task Scenario. Usability test results according to the System Usability Scale (SUS) calculations reached 86, which is at a good level (grade B) and is included in the